Impact of Culture on perceptions of landscape names - Zhang, C.; Gursoy, D.; Deng, Z.; Gao, J. (Routledge, 2015)
This study examines the impact of culture on landscape-name perceptions of tourists from China, United States, and Europe utilizing both Hofstede’s and Hall’s cultural typologies. Data for this study were collected from visitors to two national parks in China. Culture is found to have a significant impact on both sub-dimensions of understanding (legibility and coherence) and involvement (mystery and diversity). Findings suggest that tourists from different cultures are likely to interpret landscape names differently. Those from cultures with a high power distance and low individualism would prefer landscape names that are mystical, dreamy, fictive, ingenious, original, and poetic, while those from cultures with a lower power distance and high individualism would prefer names that simply describe the landscape.